Metagenomic Investigation of Idiopathic Meningoencephalomyelitis in Dogs. (2nd December 2017) - Hoon‐Hanks, L.L.; McGrath, S.; Tyler, K.L.; Owen, C.; Stenglein, M.D.
Abstract : Background: Meningoencephalomyelitis of unknown origin (MUO) is a common and life‐threatening neuroinflammatory disease in dogs. Features of the disease are suggestive of an underlying immune‐mediated process, but the association of this disease with a pathogen is still unknown. Hypothesis/Objectives: To search for candidate etiologic agent associated with cases if MUO using next generation metagenomic sequencing. Animals: Twenty‐two dogs diagnosed with either MUO (11/22; 10 CSF and 3 brain), or noninflammatory CNS diseases inconsistent with MUO (11/22; 11 CSF and 2 brain) that served as negative controls. Methods: A case control study was performed by identifying MUO and non‐MUO cases. Samples were blindly processed and then unblinded for comparative analyses. Inclusion criteria for MUO cases included consistent MRI lesions and inflammatory CSF with a negative PCR panel for infectious agents or histopathologic diagnosis. Dogs with glucocorticoid therapy within 2 weeks of sample collection were excluded. Fresh‐frozen cerebrospinal fluid (CSF; 21) and brain (5) samples were collected and RNA and DNA were extracted separately for shotgun metagenomic sequencing. Known positive samples were used as controls to validate our sequencing and analysis pipelines and to establish limits of detection. Sequencing results were analyzed at a nucleotide and protein level for broad comparison to known infectious organisms. Results: No candidate etiologic agents were identified in dogs with MUO. Conclusions and Clinical Importance: These results support but do not prove the hypothesis that MUO is not associated with infectious agents and might be an autoimmune disease.